2019
DOI: 10.3390/rs11212534
|View full text |Cite
|
Sign up to set email alerts
|

Multispectral Image-Based Estimation of Drought Patterns and Intensity around Lake Chad, Africa

Abstract: As the world population keeps increasing and cultivating more land, the extraction of vegetation conditions using remote sensing is important for monitoring land changes in areas with limited ground observations. Water supply in wetlands directly affects plant growth and biodiversity, which makes monitoring drought an important aspect in such areas. Vegetation Temperature Condition Index (VTCI) which depends on thermal stress and vegetation state, is widely used as an indicator for drought monitoring using sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 47 publications
(82 reference statements)
0
16
0
Order By: Relevance
“…Between 1973 and 1975, Lake Chad lost approximately 90% (from 24,000 to 1700 km 2 ) of its surface water. Studies have found that this decrease in water level was due to anthropogenic activities and severe droughts within that period [43,48,49]. The population around this water resource is expected to double by 2050; consequently, the demand on the lake surface water with respect to the daily and economic activities of its community is anticipated to increase [50].…”
Section: Overview Of the Study Areamentioning
confidence: 99%
“…Between 1973 and 1975, Lake Chad lost approximately 90% (from 24,000 to 1700 km 2 ) of its surface water. Studies have found that this decrease in water level was due to anthropogenic activities and severe droughts within that period [43,48,49]. The population around this water resource is expected to double by 2050; consequently, the demand on the lake surface water with respect to the daily and economic activities of its community is anticipated to increase [50].…”
Section: Overview Of the Study Areamentioning
confidence: 99%
“…In such cases, detecting differences between plants by using the NDVI becomes problematic. At the later growth stages, the vegetation aging causes the NDVI values to decline [53][54][55].…”
Section: Multispectral Indicesmentioning
confidence: 99%
“…This technique is used for environmental change detection [33] e.g. deforestation and land use change [34][35][36], identification of fire [35,37], droughts [38,39] or floods [40,41]. Three studies used shorttime image differencing to detect polar bears from space [10,24,26].…”
Section: Satellite Remote Sensing Has Recently Emerged As a New Viablmentioning
confidence: 99%